Congestion Management in a Restructured Power System Using Solar Photovoltaics - V, Subramaniyan; V, Gomathi (International Journal of Engineering and Technology, 2018)
The modern power grid is one of the most complex engineering machines in existence. There is a continuous transformation in the grid conditions that necessitate variations in the electricity production. Energy is a remarkable donor in environmental change, representing around 60 percent of the aggregate worldwide greenhouse gas outflow. Lessening the carbon force of energy, the share of non-conventional energy sources in the worldwide vitality blend is relied upon to expand supportability. So renewable energy is one of the most capable results for taking care of expanding energy demand. This paper proposed a method to lessen the congestion in the deregulated environment. The congestion in the transmission lines is identified by optimal power flow (Newton Raphson) method.  Congestion in the transmission lines is lessened by connecting a dispersed generating unit called as Solar Photovoltaic at PQ (load) bus.  A way to decide the ideal position of a Dispersed Generating unit has been suggested based on the Line Relief Sensitivity (LRS) based attitude.  The effectiveness of methodology has been validated using standard IEEE 30 bus system.